Study design for the investigation of likely aetiological factors of juvenile osteochondral conditions (JOCC) in foals and yearlings - Robert, Céline; Valette, Jean-Paul; Jacquet, Sandrine; Lepeule, Johanna; Denoix, Jean-Marie (The veterinary journal (1997), 2013)
The possible aetiology of osteochondrosis and, to a lesser extent, other developmental orthopaedic diseases or juvenile osteochondral conditions (JOCC), has been intensively investigated. However, most studies have focused on single factors of this multi-factorial disorder, or have been conducted under experimental conditions. This paper aims to present and discuss the scientific background of the BOSAC (Breeding, Osteochondral Status and Athletic Career) research program, a multi-factorial investigation on JOCC risk factors in field conditions. The epidemiology of JOCC in horses born in Normandy between 2002 and 2004 was studied. Horses were subjected to repeated body measurements, blood sampling and locomotion evaluation from birth until yearling sales. A radiographic examination, including 10 views of the limbs, was performed on each subject at approximately 6 and 17months of age. Information on nutrition and management programmes was collected by specialists from visits to the farms and the use of questionnaires. A total of 393 foals of three French breeds were monitored from birth to weaning, and 321 of these remained available for further follow-up, making the study unique as regards both the number of subjects and the variety of information collected. The study was designed to describe the evolution of JOCC, and determine possible early markers, risk factors and prognostic factors with respect to performance. Relevant data, suitable for epidemiological analyses, were collected under various field conditions that reflect current management practices in Normandy, France’s main horse breeding region.